(untitled) (Ozone Therapy Global Journal, 2018)
Dutifully, as we have been doing without interruption since 2011, we are coming to our annual meeting, publishing Volume 8, No. 1 of 2018 bilingual (Castilian and English) of the Spanish Journal of Ozone Therapy. This edition comes loaded with excellent original articles and clinical case reports. Most of them, product of the work of the doctors graduated from the Third Distance Diploma Course of "Ozone Therapy and Growth Factors" 2017/2018, organized by AEPROMO. We are proud to have an inexhaustible source of research from enthusiastic and qualified medical doctors. I take the opportunity to refer to something very serious that is happening within the Spanish scope and some other European countries that affects us directly. The General Assembly of the Collegiate Medical Organization (OMC), which represents all the Associations of Official Doctors of Spain, at its meeting of March 24th, 2017, gave the green light to an observatory board against pseudosciences, pseudotherapies, intrusive and sanitary sects. Among the therapies that have been classified as pseudoscience, is ozone therapy and they have done it without a minimum of rigor or equanimity. This decision has been executed in a biased, arbitrary way and without a minimum of dialogue or contrast of data. This is despite the fact that ozone therapy has a scientific basis and is a recognized "medical act", which must be practiced exclusively by duly trained and experienced professionals. Even in spite that ozone therapy is practiced officially in 23 public hospital in their pain management units. The superficial report of scarce 19 lines, has been developed by professionals who are completely unaware of the reality and practice of the matter they judge. At no time have they given the opportunity to give voice to the hundreds of professionals licensed in medicine who practice ozone therapy, or to the association that represents them or to the patients who receive these treatments. We have not even been given the opportunity to provide clinical studies, works or published experiences, to defend ourselves. We have been sentenced without hearing the medical doctors who practice a "recognized medical act" such as ozone therapy.